Handbook of research on reading comprehension - Israel, Susan E. (New York The Guilford Press, 2017)
"This edition provides a transformative snapshot of reading comprehension as a field of study at a seminal moment. It maintains the same high level of standards with respect to (1) historical perspectives useful for laying the foundation of study on reading comprehension; (2) theoretical perspectives that allow the reader to consider different views on how specific areas have evolved since the first edition; (3) excellent chapters on various elements of reading comprehension, including major research studies in assessment, cultural impacts of reading comprehension, issues affecting English language learners, and consideration of international populations; and (4) identification of future research needs to help raise important questions and stimulate possible hypotheses for future research"--Provided by publisher.
I. Historical Analysis. Introduction: The Consequential Pulse of Reading Comprehension Research / Susan E. Israel and D. Ray Reutzel -- The Roots of Reading Comprehension Instruction / P. David Pearson and Gina N. Cervetti -- Comprehension Is Not Simple: Considering the Persisting Dangers in the Simple View of Reading Comprehension / James V. Hoffman -- Professional Learning for Educators Focused on Reading Comprehension: A Historical Perspective / Barbara Laster and Carla Finkelstein -- Research on Helping Readers Make Sense of Print: Evolution of Comprehension-Based Pedagogy / Kenneth S. Goodman, Yetta M. Goodman, and Kelly L. Allen -- II. Theoretical Perspectives. An Evolving Perspective of Constructively Responsive Reading Comprehension Strategies in Multilayered Digital Text Environments / Byeong-Young Cho and Peter Afflerbach -- Toward a Theory of Literacy Meaning Making within Virtual Worlds / Richard Beach and Robert J. Tierney -- Meaning Making in the 21st Century: The Sociogenesis of Reading Comprehension / James R. Gavelek and Colleen E. Whittingham -- Literacy, Comprehension, and Neurosciences / George G. Hruby -- III. Diagnosis, Assessment, and Intervention. Assessments of Reading Comprehension: Challenges and Directions / Lauren Leslie and JoAnne Schudt Caldwell -- Using Assessments to Map and Evaluate the Comprehension Development of Young Children / Katherine A. Dougherty Stahl and Georgia Earnest García -- Comprehension Difficulties and Struggling Readers / Richard L. Allington and Anne McGill-Franzen -- Self-Regulation and Reading Comprehension: Moving Beyond the Individual's Cognition in Regulated Learning / Dixie D. Massey and Samuel D. Miller -- Reconsidering Fluency's Role in Reading Comprehension / Melanie Kuhn and Paula J. Schwanenflugel -- IV. Impact of Text and Higher-Order Processing. Text and Comprehension: A Retrospective, Perspective, and Prospective / Emily Fox and Patricia A. Alexander -- Reading Comprehension in the Middle Grades: Characteristics, Challenges, and Effective Supports / Ruth Wharton-McDonald and Joy Erickson -- Vocabulary and Reading Comprehension: The Nexus of Meaning / Gwynne Ellen Ash and James F. Baumann -- Improving Adolescent Comprehension: Developing Comprehension Strategies in the Content Areas / Mark W. Conley -- Structure, Epistemology, and Metalanguage Foundations of Reading Comprehension in Scientific Texts / Linda M. Phillips and Anat Yarden -- Graphic Text and Visual Literacies in Reading Comprehension / Stergios Botzakis, Jason D. DeHart, and Sean P. Connors -- V. Diverse Components and Engagement. Reading Comprehension Research and the Shift toward Culturally Sustaining Pedagogy / Colleen M. Fairbanks, Jewell E. Cooper, Sandra M. Webb, and Lynn A. Masterson -- Comprehension in the Disciplines / Cynthia Shanahan -- Constructing Meaning through Discussion / Keli Garas-York and Janice F. Almasi -- The Role of Interest in Reading Comprehension / Sheree E. Springer, Janice A. Dole, and Douglas J. Hacker -- Comprehension Strategies Instruction for Learners of English: Where We Have Been, Where We Are Now, Where We Still Might Go / Rachel Brown -- Family Literacy Initiatives and Reading Comprehension / Patricia A. Edwards, Maria Selena Protacio, Marliese Peltier, and Laura Hopkins -- VI. Future Directions. The Role of Literacy Coaching in Improving Comprehension Instruction / Misty Sailors, Sylvia Minton, and Lorena Villarreal -- Public Policy in an Era of Changing Literacies: A Focus on Reading Comprehension / Lori Helman and Cory Stai -- Sophistication of Reading Comprehension: Where to from Here? / Susan E. Israel.
Includes bibliographical references and index.
Keywords: Reading comprehension -- Handbooks, manuals, etc; Reading